Elite perceptions of poverty and inequality - Moore, Mick; Reis, Elisa Pereira
Drawing on case studies from a range of developing countries, the contributors to this volume discover major differences in how national elites understand and represent poverty. The classic threats that induced elites in late 19th century Europe, such as the fear of crime, epidemics, military weakness or political unrest--do not feature prominently in the consciousness of most developing country elites. Nor do most of them believe that there is a viable solution to poverty through public action. The findings help to explain the relative ineffectiveness of poverty reduction strategies so far, and illustrate the need to present poverty in ways that tie in with how national elites understand their world.--Publisher description.